Application model of students team achievement division (stad) in English class - Ely Trianasari; Ika Yuniwati (English, 2019)
This study aims to increase the participation and learning achievement of English through the application of cooperative learning models of the Student Teams Achievement Division (STAD) type. This type of research is Classroom Action Research (CAR) which is carried out collaboratively with peers. This research was carried out in two cycles consisting of 4 stages, namely planning, implementing, observing, and reflecting. The subjects of this study were English lecturers and second semester students consisting of 29 people. Data collection methods use subjective tests and observations. Subjective tests are used to measure learning achievement while observation sheets aim to observe the activities of students and lecturers. Quantitative data were analyzed using quantitative descriptive, while qualitative data were analyzed qualitatively qualitative. The results of the study obtained the initial data of students considered as complete category as many as 5 people or the percentage of classical completeness of 17.24%. In the first cycle, students considered as complete category as many as 9 people with a percentage of classical completeness of 31.03%. While the second cycle is the number of students considered as complete category as many as 24 people, with a percentage of classical completeness of 82.76%. The conclusion of the results of the research carried out, namely the application of cooperative methods STAD type in the learning process can improve student participation and learning achievement in English language courses in mechanical engineering department.